JSPC 2020
DOI: 10.26650/jspc.2020.79.0002
|View full text |Cite
|
Sign up to set email alerts
|

Göçün Suriyeli ve Yemenli Göçmenlerin Aile Yapıları Üzerine Etkileri

Abstract: Bu araştırma, Suriye ve Yemen'de yaşanan iç karışıklıklar, savaş, siyasi baskı vb. nedenlerle İstanbul'a göç etmiş ve İstanbul/Beylikdüzü ilçesinde ikamet eden Suriyeli ve Yemenli göçmenlerin aile yapısındaki değişim ve dönüşümleri; ekonomik, sosyo-kültürel, eğitim, sağlık ve barınmaya ilişkin incelemek ve değerlendirmek amacıyla yapılmıştır. Nitel araştırma yöntemlerinin kullanıldığı bu çalışmada, belirtilen nedenlerle İstanbul'a göç etmiş ve İstanbul/Beylikdüzü ilçesinde ikamet eden Suriyeli ve Yemenli 14 gö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Migration is a challenging and multidimensional process. In this process, refugees might face psycho-social, economic, education, and health-related problems [14]. These problems may create stress on refugees, and they may suffer a lot from the negativities of the process [15].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Migration is a challenging and multidimensional process. In this process, refugees might face psycho-social, economic, education, and health-related problems [14]. These problems may create stress on refugees, and they may suffer a lot from the negativities of the process [15].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, the most important issue for immigrants was employment (Koç et al, 2015). Ekmen and Koçak (2020) found that migration involves social change and affects immigrants' social and cultural lives. Their participants were affected by all types of social issues, such as relationships in the neighborhood, food culture, style of dressing, family structure or type, family roles, and responsibilities, among others.…”
Section: Discussionmentioning
confidence: 99%
“…If integration problems occur, immigrants can stubbornly oppose locals and vice versa. If the migration policy has not been implemented correctly and inspections have not been conducted effectively, the immigrant population may find itself underpaid and without insurance (Ekmen & Koçak, 2020). By contrast, free services for immigrants might result in a high cost to the host country, causing locals to respond negatively to immigrants (Karakaya, 2020).…”
Section: Effects On the Host Countrymentioning
confidence: 99%